Handbook of Heterocyclic Chemistry (3rd Edition) - Katritzky, Alan R. (Elsevier, 2010)
Heterocyclic compounds play a vital role in the metabolism of living cells. Their practical applications range from extensive clinical use to fields as diverse as agriculture, photography, biocide formulation and polymer science. Written by leading scholars and industry experts, this book is thoroughly updated with over 50% new content. It has been rewritten with a new expanded author team, who have carefully distilled essential information on the reactivity, structure and synthesis of heterocycles from the 2008 major reference work Comprehensive Heterocyclic Chemistry III. To bring the work up to date the author team have also added new synthetic examples and structures, key applications and new references from 2008-2010.